2014
DOI: 10.2340/00015555-2344
|View full text |Cite
|
Sign up to set email alerts
|

Teledermoscopy in High-risk Melanoma Patients: A Comparative Study of Face-to-face and Teledermatology Visits

Abstract: Teledermoscopy is considered a reliable tool for the evaluation of pigmented skin lesions. We compared the management decision in face-to-face visits vs. teledermatology in a high-risk melanoma cohort using total-body photography, macroscopic and dermoscopic images of single lesions. Patients were assessed both face-to-face and by 4 remote teledermatologists. Lesions identified as suspicious for skin cancer by face-to-face evaluation underwent surgical excision. The teledermatologists recommended "self-monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 39 publications
(40 reference statements)
0
41
0
3
Order By: Relevance
“…However, TD has proven to be comparable with face-to-face review in accuracy rates concerning management and clinical outcomes. 6,7 Approximately 60% of studies showed better diagnostic accuracy of TD compared with clinic care. 8 To obtain the views of British dermatologists on TD an electronic questionnaire was submitted to all British Association of Dermatologists (BAD) members (1532 total, 818 consultants) in September to October 2016.…”
mentioning
confidence: 99%
“…However, TD has proven to be comparable with face-to-face review in accuracy rates concerning management and clinical outcomes. 6,7 Approximately 60% of studies showed better diagnostic accuracy of TD compared with clinic care. 8 To obtain the views of British dermatologists on TD an electronic questionnaire was submitted to all British Association of Dermatologists (BAD) members (1532 total, 818 consultants) in September to October 2016.…”
mentioning
confidence: 99%
“…In total, 40 201 patients were teleconsulted over 14 years using our service. To our knowledge, this is by far the largest patient group and longest study on TD published from the UK, and one of the largest datasets reported globally . Additionally, to the best of our knowledge, this is the first study documenting data from an integrated TD service led by secondary care National Health Service (NHS) dermatology services.…”
Section: Discussionmentioning
confidence: 92%
“…Benefits of TD include reduction in waiting lists, cost, patient travel and unnecessary referrals . Contrary to early beliefs, TD has been shown in multiple studies to be comparable to face‐to‐face review in accuracy rates of diagnosis, management and clinical outcomes …”
Section: Introductionmentioning
confidence: 99%
“…Al revisar lo descrito en la literatura científica, en nuestro estudio, el índice kappa para la clasificación de las lesiones y la recomendación terapéutica tuvo un excelente desempeño. Se han reportado índices kappa casi perfectos entre la evaluación teledermatoscópica y la evaluación presencial, cuando los teleevaluadores eran dermatólogos expertos en dermatoscopia (21) . Incluso, se ha descrito un mejor rendimiento diagnóstico por teledermatoscopia que mediante la evaluación presencial, usando como prueba de referencia la histopatología cuando los teleevaluadores tenían mayor experiencia (5,7) .…”
Section: Tabla 1 Características Demográficas: Análisis Descriptivounclassified